2015
DOI: 10.1016/j.psychres.2015.06.033
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between patients’ and caregivers’ beliefs about the causes of schizophrenia and clinical outcomes in Latin American countries

Abstract: Beliefs about the causes of schizophrenia are thought to impact treatment outcomes. We investigated 3 theoretically opposing belief systems (biological, psychosocial, magical-religious) in relation to the severity of positive and negative symptoms and to attitudes towards medications. We recruited 253 patients with schizophrenia and their primary caregivers from public mental health clinics in Bolivia, Chile, and Peru. We assessed patients’ and caregivers’ beliefs about the causes of schizophrenia, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“… 59 Previous studies reported the importance of respecting and considering patients’ belief systems to improve medication attitudes. 22 Other sociodemographic and clinical variables were not related to adherence, as obtained by Lacro et al 5 This result is similar to previous studies as well that the side effects to the medication had impact on DAI-10 scores. 11 , 17 , 63 65 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 59 Previous studies reported the importance of respecting and considering patients’ belief systems to improve medication attitudes. 22 Other sociodemographic and clinical variables were not related to adherence, as obtained by Lacro et al 5 This result is similar to previous studies as well that the side effects to the medication had impact on DAI-10 scores. 11 , 17 , 63 65 …”
Section: Discussionsupporting
confidence: 89%
“…Other differences are associated with psychiatric care facilities: per 100,000 inhabitants, Bolivia has 0.1 psychiatric hospitals, Peru has 0.01, and Chile has 0.003 (this country has a greater number of outpatient institutions), mental health staff (the number of psychiatrists in Bolivia is 0.1; Peru: 0.1 and Chile: 0.6 per 100,000 inhabitants); lack of day hospitals (Bolivia, 0.1; Peru, 0; and Chile, 0.5), and residential care (Bolivia, 0; Peru, without data; and Chile, 103). 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Casual beliefs are known to influence an individual's health status, management behaviors, lifestyle decisions, and disease outcomes (Caqueo‐Urízar, Boyer, Baumstarck, & Gilman, ; Fleary & Ettienne, ; Petrie, Jago, & Devcich, ; Wisdom & Green, ). The majority of child participants felt that factors beyond their control, such as genetics, were responsible for their symptoms; this is not surprising, given that most patients are counseled that hEDS is a genetic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown an association between carer and consumer attitudes about their illness or treatment and found that carer attitudes can impact consumer outcomes. A Latin American study of consumers with schizophrenia and their carers investigated the association between causal belief of schizophrenia with attitudes toward medicine and symptoms (Caqueo-Urizar et al, 2015). Consumer and carer causal beliefs shared small to moderate correlations (e.g., biological causal belief r=.45).…”
Section: Introductionmentioning
confidence: 99%